Analysis of Factors Influencing the Welfare of Fishermen in Lake Sentani, Jayapura Regency - Rachmaeny Indahyani; Halomoan Hutajulu; Great Aldegonda; Vanessa Devina P. Pangke (Westscience Press, 2025)
This study examines the socio-economic conditions of fishermen in Lake Sentani, Jayapura Regency, with a focus on challenges and local wisdom-based strategies to improve their welfare. Lake Sentani, as a major natural resource, has great potential in the fisheries and tourism sectors, but fishermen face problems such as resource exploitation, pollution, and limited access to technology. This study used multiple regression analysis. The results show a dependence on traditional fishing, low productivity, and capital and marketing constraints. Factors such as education, experience, capital, and access to facilities significantly influence fishermen's welfare. Existing fisheries policies remain weak in terms of socialization and oversight. To improve welfare, income diversification, technology adoption, and capacity building for fishermen are needed. Local wisdom-based strategies include pollution management, zoning management, business literacy, and the development of environmentally friendly and sustainable local fisheries value chain-based business models. Collaboration between business actors and digital technology is crucial to expanding markets and improving fishermen's welfare.⁠